Contextual Teaching Learning (CTL) Learning Through School Media Environment Utilization To Improve Literacy Of Science And Achievement Test - Mia Hilmiyati; Anna Fitri Hindriana; Sri Redjeki (Edubiologica Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2018)
The study of X grade biology in high school shows that teachers have not utilized the school environment such as school garden and school field as a medium of learning. School environments are potentially exploited for learning on biodiversity materials, because school environments have a lot of plant diversity in both gene, species and ecosystem levels, as well as the students' science literacy skills are still low that affect student learning outcomes. Therefore overcome these problems one of them is by applying the learning that can cover the science not only from the side of theory, but from the application also is the learning of CTL combined with the utilization of school environmental media. The purpose of this study is to increase the ability of science literacy and to know the improvement of students' cognitive achievement after using CTL learning through the utilization of school environment media on the material of plant biodiversity. The research design used was pre test-post test control group design. In this research design there are two groups selected by purposive sampling, that is group of X grade MIPA-2 as experiment class and  X grade MIPA-1 as control class. Based on the results of research and data analysis, the average gain of science literacy is 0.63 point for the control class seen as the medium category and the average gain for the experimental class is 0.80 point seen as the high category. It means that CTL program through school media environment gives an improfement to science literacy of student, While the average of gain students' cognitive achievement score is  0.29 point for control class see as low category and 0,68 for experiment class seen as medium category. It means that CTL program through school media environment gives an improvment to student’s cognitive achievement. The result of hypothesis testing on posttest data of science literacy, t count t table (8,829 2.015) there is significant difference of posttest value between experiment class and control class. Whereas in posttes data of learning result t value t table (8,763 2.015) there is difference significantly mean posttes value, between experiment class and control class. Observation result of CTL learning implementation through utilization of school environment media can be done very well, at inquiry stage with percentage of 88%, community learning stage 87%, questioning stage 87%, real assessment stage 88%. The result of questionnaire of student response to this learning gave interesting response with value 80%Keywords: CTL learning; School environmental media; Science literacy; Achievement test